Giving Super Bubbles Play Therapy to Reducing Anxiety in Children Due to Hospitalization at Gambiran Hospital, Kediri City - Nur Yeny Hidajaturrokhmah; Angelina Madeira; Kaeleen Dingle (Universitas STRADA Indonesia, 2022)
Background: Problems that often arise due to hospitalization in children include feelings of anxiety and stress, separation from their parents during treatment at the hospital. Purpose: The purpose of this study was to determine the effect of super bubbles play therapy on anxiety due to hospitalization in children in the Galuh Room at Gambiran Hospital, Kediri. Methods: The design of this study was pre-experimental with one group pre-post test design. Respondents were taken by purposive sampling technique. The population studied were all children who were treated in the Galuh Room at Gambiran Hospital, Kediri City with a sample of 30 people. The independent variable studied was super bubbles play therapy and the dependent variable was anxiety due to hospitalization in children. The results were analyzed using the Wilcoxon statistical test. Results: The results showed that before being given therapy playing super bubbles most respondents with anxiety due to hospitalization in the heavy category as many as 20 (67%) respondents. After being given super bubbles play therapy almost all respondents in the mild category as many as 23 (77%) respondents. The results of data analysis show that the level of significance 0.000 ? 0.05 so H0 is rejected and H1 is accepted. Conclusion: Therefore, there is an effect of super bubbles play therapy on anxiety due to hospitalization in children in the Galuh Room, Gambiran Hospital, Kediri. Based on the results of the study it was concluded thatsuper bubbles bermain play therapy have an influence on anxiety due to hospitalization in children.